2006
DOI: 10.1126/science.1118420
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comment on "Iron Isotope Constraints on the Archean and Paleoproterozoic Ocean Redox State"

Abstract: We reported a secular trend in iron isotope values of Precambrian sedimentary pyrite and related it to the changing redox state of Precambrian oceans. We restate that the iron cycle before 1.8 billion years ago was different from that now and reflected the rise of atmospheric oxygen and the subsequent moderate atmospheric oxygen level in the Paleoproterozoic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In this context, partial oxidation associated with BIF precipitation would have left a residue of isotopically light Fe(II) aq (<À0.15‰/amu). Yamaguchi and Ohmoto (2006) and Archer and Vance (2006) questioned this interpretation and suggested instead that the light Fe isotopic compositions measured in >2.3 Ga pyrite grains reflect microbial cycling of Fe in the sediment by dissimilatory iron reduction (however, see Rouxel et al, 2006). Studies of shallow sediment profiles (Severmann et al, 2006;Staubwasser et al, 2006) have shown that such redox cycling does occur in present-day sediments, producing Fe(II) aq in porewaters with F Fe as low as À1.5‰/amu.…”
Section: The Fe Isotopic Composition Of Eoarchean Seawatermentioning
confidence: 88%
“…In this context, partial oxidation associated with BIF precipitation would have left a residue of isotopically light Fe(II) aq (<À0.15‰/amu). Yamaguchi and Ohmoto (2006) and Archer and Vance (2006) questioned this interpretation and suggested instead that the light Fe isotopic compositions measured in >2.3 Ga pyrite grains reflect microbial cycling of Fe in the sediment by dissimilatory iron reduction (however, see Rouxel et al, 2006). Studies of shallow sediment profiles (Severmann et al, 2006;Staubwasser et al, 2006) have shown that such redox cycling does occur in present-day sediments, producing Fe(II) aq in porewaters with F Fe as low as À1.5‰/amu.…”
Section: The Fe Isotopic Composition Of Eoarchean Seawatermentioning
confidence: 88%
“…For example, the highly variable and negative δ 56 Fe values of pyrite during Stage I may reflect reservoir effects in ocean Fe resulting from the removal of isotopically heavy Fe during oxidative precipitation to form banded iron formations or disseminated in marine sediments on continental shelves (Rouxel et al 2005). Similarly, the positive δ 56 Fe values in the intermediate Stage II might be related to the increased effect of sulfide precipitation in a redox-stratified ocean (Rouxel et al 2006a). Such interpretations indicate that Fe isotope variations in sedimentary pyrite are particularly sensitive to the dissolved Fe(II) concentration in seawater, and hence they can be used to place important constraints on the oxygenation of ancient oceans.…”
Section: Ironmentioning
confidence: 99%
“…doi:10. 1016/j.gca.2008.04.035 Mars, and the mobility of a host of contaminants in modern earth settings (Straub et al, 2001;Benison and LaClair, 2003;Edwards et al, 2004;Emerson and Weiss, 2004;Kappler and Newman, 2004;Roden et al, 2004;Ferris, 2005;Kump and Seyfried, 2005;Rouxel et al, 2005;Rouxel et al, 2006;Yamaguchi and Ohmoto, 2006;Stucki et al, 2007;Neubauer et al, 2008). In any of these environments geochemical control on microbial ecology can be manifested in diverse ways, but one key factor is to consider the rates at which organisms can utilize existing substrates including electron donors and acceptors to garner energy for growth.…”
Section: Introductionmentioning
confidence: 99%